EFEKTIFITAS KINERJA GURU DAN SISTEM MANAJEMEN KURIKULUM TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR INPRES 133 BUMI AJO KABUPATEN SORONG SELATAN - Zamzamah, Siti; Komber, Mervin I.S.; Irwan, Andi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effectiveness of teacher performance and the curriculum management system in improving the quality of education at the elementary school level, specifically at Inpres 133 Elementary School, Bumi Ajo, South Sorong Regency. Basic education is a crucial foundation for developing quality human resources. The quality of education at the elementary school level is significantly influenced by various factors, including the quality of teacher performance and the effectiveness of the curriculum management system implemented in the school. This study employed a qualitative approach. This approach was used to gain a deeper understanding of the phenomena occurring in the field related to the effectiveness of teacher performance and the curriculum management system in improving the quality of education. Data collection techniques used in this study included observation, in-depth interviews, and documentation. The research informants consisted of the principal, teachers, and other parties involved in educational management at Inpres 133 Elementary School, Bumi Ajo, South Sorong Regency. The data obtained were then analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results of this study conclude that the effectiveness of teacher performance and the curriculum management system play a crucial role in improving the quality of education at Inpres 133 Elementary School, Bumi Ajo, South Sorong Regency. The synergy between professional teacher performance, participatory principal leadership, and systematic curriculum management is a key factor in creating a quality learning process. Efforts to improve education quality require ongoing efforts through enhancing teacher competency, strengthening curriculum management, and policy support from the government and education stakeholders.